1996
DOI: 10.1055/s-2007-1006630
|View full text |Cite
|
Sign up to set email alerts
|

Is Axonal Sprouting Able to Traverse the Conjunctival Layers of the Peripheral Nerve? A Behavioral, Motor, and Sensory Study of End-To-Side Nerve Anastomosis

Abstract: The repair of large peripheral nerve defects is not always possible, especially when the proximal stump is not available. In these cases, end-to-side nerve anastomosis has been proposed. In the present experiment, using the terminal branches of the rat brachial plexus, the authors studied behavioral responses after end-to-side nerve anastomoses using fibrin glue, 3 and 6 months after surgery. Rats were evaluated by results of a grasping test, a capsaicin test and a hot-plate test. The collected data demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0
7

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 4 publications
2
64
0
7
Order By: Relevance
“…The fibrin glue, already used in the ETE [19][20][21][22][23] , can also be used in the ETS 4 . An important disadvantage of this method is it high cost 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fibrin glue, already used in the ETE [19][20][21][22][23] , can also be used in the ETS 4 . An important disadvantage of this method is it high cost 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Since Viterbo et al [1][2][3] introduced the End-to-Side Neurorraphy (ETS) concept without lesion in the donor nerve, many studies were published 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…While most investigators believe that an epi-or perineurotomy is required for axons to sprout through an ETS nerve repair (Bertelli, et al 1996, Noah, et al 1997, others suggest that effective sensory axonal sprouting into the ETS repair occurs in the absence of any donor nerve injury. In this aforementioned study, a silicone Y-chamber that secured the donor and recipient limbs to one another facilitated sensory sprouting as attributed to the invasion of donor nerve epineurium with SCs (Matsumoto, et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested that collateral axonal sprouts repopulate the terminal limb without axotomy, attributing this spontaneous phenomenon to neurotrophic influences (Caplan, et al 1999,Thanos, et al 2001. Others suggest that an epineurotomy or perineurotomy, exposing but not injuring donor axons facilitates spontaneous collateral sprouting (Bertelli, et al 1996). Others show that regenerative sprouting induced by a deliberate axotomy is required to induce some terminal sprouts to regenerate down the recipient pathway rather than the original donor nerve pathway ).…”
Section: Introductionmentioning
confidence: 99%
“…One way is that the regenerative nerve derived from collateral sprouting from the intact donor nerve [53][54][55]. The other is that regenerated nerve derived from terminal sprouting of donor nerve due to the damage to the donor nerve during suturing process [56][57][58]. Zhang, et al [59] and Hayashi, et al [60] demonstrated that the nerve regeneration through the terminolateral neurorrhaphy originated from the collateral sprouting from the intact donor nerve by using immunofluorescence tracing technique.…”
Section: The Mechanism Of Nerve Regeneration Of Terminolateral Neurormentioning
confidence: 99%